ASOSIASI BURUNG JULANG SULAWESI (Rhyticeros cassidix) DENGAN POHON EBONI (Diospyros celebica Bakh) DI CAGAR ALAM PANGI BINANGGA DESA PANGI KABUPATEN PARIGI MOUTONG - Mangi, Herianto; Ningsih, Sri; Ihsan, Moh (Jurnal Warta Rimba, 2013)
Julang Sulawesi birds (Rhyticeros cassidix) and ebony tree (Diospyros celebica Bakh) are protected sulawesi endemic species and the both species be found in the Pangi Binangga Nature Reserve. Julang sulawesi bird is a fruit-eating birds species including ebony fruit. The purpose of this research is to determine the association of julang sulawesi birds (Rhyticeros cassidix) with ebony tree (Diospyros celebica Bakh) in the area of Pangi Binangga Nature Reserve, Moutong Parigi District. This research was conducted in three months starting from May to July 2013. This research uses the transect method that is make make 20x20 meter plots for 20 plots and placed parallel along side the 500-meter transect. The research was conducted at the time where ebony trees are not in fruiting season, there is interaction in which the julang sulawesi birds utilize ebony tree as a resting place on the analysis using of chi-square X2 however it was found that julang sulawesi birds (Rhyticeros cassidix) and ebony tree (Diospyros celebica Bakh) are not associated. Keywords : Association, julang sulawesi bird (Rhyticeros cassidix), trees ebony (Diospyros celebica Bakh)